Electromagnetic Vibration Energy Harvesting for Railway Applications - Bradai S.; Naifar S.; Viehweger C.; Kanoun O. (MATEC Web of Conferences, 2018)
Safe localization of trains via GPS and wireless sensors is essential for railway traffic supervision. Especially for freight trains and because normally no power source is available on the wagons, special solutions for energy supply have to be developed based on energy harvesting techniques. Since vibration is available in this case, it provides an interesting source of energy. Nevertheless, in order to have an efficient design of the harvesting system, the existing vibration needs to be investigated. In this paper, we focus on the characterization of vibration parameters in railway application. We propose an electromagnetic vibration converter especially developed to this application. Vibration profiles from a train traveling between two German cities were measured using a data acquisition system installed on the train’s wagon. Results show that the measured profiles present multiple frequency signals in the range of 10 to 50 Hz and an acceleration of up to 2 g. A prototype for a vibration converter is designed taking into account the real vibration parameters, robustness and integrability requirements. It is based on a moving coil attached to a mechanical spring. For the experimental emulation of the train vibrations, a shaker is used as an external artificial vibration source controlled by a laser sensor in feedback. A maximum voltage of 1.7 V peak to peak which corresponds to a maximum of 10 mW output power where the applied excitation frequency is close to the resonant frequency of the converter which corresponds to 27 Hz.